Changes in magnetic resonance imaging before and after autologous stem cell transplantation correlate with response and survival in multiple myeloma - Hillengaß, Jens; Shah, Sofia; Kilk, Kerstin; Weber, Marc-André; Hielscher, Thomas; Hose, Dirk; Delorme, Stefan; Goldschmidt, Hartmut; Neben, Kai (Haematologica, the hematology journal, 2012)
In multiple myeloma, focal lesions, as well as diffuse and variegated infiltration patterns, can be detected by magnetic resonance imaging. In the current study, we compared treatment response in 100 myeloma patients with changes in infiltration patterns in whole body magnetic resonance imaging before and after autologous stem cell transplantation. We found an agreement between serological response and changes in imaging (P<0.001). In detail, a significant agreement of treatment response was observed for diffuse (P=0.004) as well as for focal (P=0.01) infiltration patterns. The number of focal lesions at second magnetic resonance imaging was of prognostic significance for overall survival (P=0.001). We conclude that treatment response in myeloma goes along with a decrease in imaging findings. We suggest that residual disease after high-dose chemotherapy detected by magnetic resonance imaging increases the risk of relapse. Therefore, myeloma patients with such findings after treatment might benefit from further cytoreduction.
Gesehen am 21.06.2018